perancangan bangunan olahraga ekstrim di jakarta - Galang Firmansyah; Harfa Iskandaria (FAKULTAS TEKNIK UNIVERSITAS BUDI LUHUR, 2020)
Extreme sports area is an extreme sports area where sports activists from among children, adolescents, and adults this extreme sport stimulates adrenaline and tends to display speed, height, danger and actions that require courage. Special buildings are used for athletes and competitions during the last part of the outdoor activities are used as areas that are common to visitors. This extreme sports area provides skateboar buildings, freestyle bikes, trampoline, and wall climbing in addition to that there are supporting activities. The concept of the building uses the concept of Deconstruction which is a development / revival of modern architecture. The purpose of using this concept of deconstruction architecture is that the buildings and functions of the buildings in the buildings are harmonious.